Phenological Attributes of some Tree Species from Indroda Park, Gandhinagar, Gujarat, India - Dave, Monika; Nakar, R.N.; Punjani, Bhasker L. (Indian Forester, 2024)
Phenological observations were carried out on twenty five woody tree species of fourteen different families in Indroda Nature Park, Gandhinagar in Gujarat state. Gandhinagar is positioned between 20Â°6’ N to 24Â°42’ N latitude and 68Â°10’ E to 74Â°28’ E longitude where twenty five selected tree species were tagged and observed twice in a month for consecutive three years from January 2019 to December 2021. Main four phenophages were observed i.e., new foliage, leaf fall, flowering and fruiting respectively. Percent species in phenophase and average number of approximate days were calculated for detailed study. Maximum new foliage was recorded in 22 species (2019), 16 species (2020 and 2021) respectively and found in August month. Maximum leaf fall was recorded in 15 species (2019), 16 species (2020 and 2021) respectively and found during January month. 17 species (2019), 19 species (2020 and 2021) showed flowering during month of April. In fruiting event, maximum fruiting in 22 species (2019 and 2021), 23 species (2020) was noted in May month. Average deviation in new foliage and leaf fall were Â± 1.45 days and Â± 4.61 days respectively. On the other hand, deviation in flowering was Â± 5.42 days and in fruiting there was Â± 6.82 days. Positive and negative correlation among different phenological traits and environmental parameters showed that there is significant association between tree phenology and existing environment. If any change occurs in environment, there will be its impact on phenological behavior. This type of research holds significant value in comprehending how plant species adapt, proving invaluable for fields like physiology, ecology and forestry.